2019
DOI: 10.1039/c8ob01895b
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in homogeneous borrowing hydrogen catalysis using earth-abundant first row transition metals

Abstract: The review highlights the recent advances (2013-present) in the use of earth-abundant first row transition metals in homogeneous borrowing hydrogen catalysis. The utility of catalysts based on Mn, Fe, Co, Ni and Cu to promote a diverse array of important C-C and C-N bond forming reactions is described, including discussion on reaction mechanisms, scope and limitations, and future challenges in this burgeoning area of sustainable catalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
129
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(138 citation statements)
references
References 50 publications
1
129
0
Order By: Relevance
“…[12] On the contrary, β-hydrogen elimination is relatively frequent for alkoxides and constitutes the basis for a number of catalytic applications mentioned in the Introduction. [17][18][19][20] Mechanistic studies have shown that βhydrogen elimination may, in fact, involve different pathways, summarized in Scheme 10. Mechanism A is analogous to typical β-elimination in alkyl complexes, and requires a vacant coordination site in cis to the β-hydrogen donor ligand.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[12] On the contrary, β-hydrogen elimination is relatively frequent for alkoxides and constitutes the basis for a number of catalytic applications mentioned in the Introduction. [17][18][19][20] Mechanistic studies have shown that βhydrogen elimination may, in fact, involve different pathways, summarized in Scheme 10. Mechanism A is analogous to typical β-elimination in alkyl complexes, and requires a vacant coordination site in cis to the β-hydrogen donor ligand.…”
Section: Methodsmentioning
confidence: 99%
“…[65] Our ability to synthesize a range of nickel alkoxide and amide complexes prompted us to examine the thermal stability of these complexes, in order to gain some insight in their decomposition mechanisms. In one of our studies (Scheme 12) we compared the thermal stability of some methylnickel alkoxides and amides (18)(19)(20)(21), available through the fluoride exchange route described in the precedent section. [66] To complete this study, we included a mixed methylnickel alkyl, 22, also obtained through fluoride exchange method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These examples show that the iron‐catalysed borrowing methodology exhibits similar efficiency to that with other 3d transition metals, but they are not yet as competitive as the classical noble metal‐catalysed ones, mainly in terms of catalytic loadings …”
Section: Multi‐step Reactions Involving Iron‐catalysed Hydrogen Bomentioning
confidence: 97%
“…The borrowing hydrogen strategy has been widely applied in organic transformations to construct various C-X (X = C, N, S) compounds in the last decade [17][18][19]. In this context, of particular importance is the N-alkylation of amines with alcohols to synthesize structurally complex primary and/or secondary amine compounds, which represents one of the most straightforward, efficient and eco-friendly methodologies for amine synthesis.…”
Section: Introductionmentioning
confidence: 99%